Development of Preventive Dentistry Practicum Guide Module for D – IV Dental Nursing Department Students, Health Polytechnic, Ministry of Health, Jambi - Febrianti, Sri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This research aims to develop a Preventive Dentistry practice guide module as a learning aid for students of the Dental Nursing Department at the Jambi Health Polytechnic. This research uses research and development methods involving various stages such as needs analysis, teaching material development, expert validation, and field trials. The research sample involved third semester students of the Dental Nursing Department for the 2017-2018 academic year, Jambi Health Polytechnic. Data was collected through student achievement assessments, questionnaires, and expert validation. The validation results show that the module developed meets the criteria for clarity of learning objectives, availability of practicum tools and materials, consistency of writing, and suitability of images/photos with practicum material. Based on input and suggestions from material experts and design experts, revisions were made to the module to improve its quality. It is hoped that this module can help students understand and apply Preventive Dentistry material more effectively and efficiently.